2019
DOI: 10.1038/s41598-019-50559-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between menstrual cycle irregularity and tinnitus: a nationwide population-based study

Abstract: This population-based cross-sectional study investigated the association between menstrual cycle irregularity and tinnitus in premenopausal Korean women. We used data from the 5th Korea National Health and Nutrition Examination Survey (2010–2012). A total of 4633 premenopausal women were included. Hierarchical multivariable logistic regression analysis was performed. Individuals with tinnitus accounted for 21.6%. Women with tinnitus or menstrual irregularity had significantly higher rates of stress, depressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…Manual review of v-safe responses suggested some reports of breast tenderness, mood changes, and tinnitus; these symptoms could be related to hormonal changes, which could disrupt normal menstruation, menopause, or pre-existing amenorrhea secondary to medications or other medical conditions. 24 Menstrual cycle prolongation has been associated with receiving two COVID-19 vaccine doses within the same cycle, 12 supporting the hypothesis that immune response to vaccination can affect the hypothalamic–pituitary–ovarian axis. Temporary menstrual irregularities have been reported after SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 91%
“…Manual review of v-safe responses suggested some reports of breast tenderness, mood changes, and tinnitus; these symptoms could be related to hormonal changes, which could disrupt normal menstruation, menopause, or pre-existing amenorrhea secondary to medications or other medical conditions. 24 Menstrual cycle prolongation has been associated with receiving two COVID-19 vaccine doses within the same cycle, 12 supporting the hypothesis that immune response to vaccination can affect the hypothalamic–pituitary–ovarian axis. Temporary menstrual irregularities have been reported after SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 91%
“…Included records were published across 1992-2023. We found notable variation in the use of terms to describe suicidal ideation and behaviours (e.g., "suicide wishes" [41], "unsuccessful suicide attempts… successful suicide attempts" [8], "committed suicide" [42] "committing suicide" [43][44][45]. In reporting on the primary studies catalogued, terminology used by authors was retained to present their findings accurately.…”
Section: Resultsmentioning
confidence: 99%
“…Manifestations of PMS include mood swing, irritability, depression, anger, anxiety, insomnia, breast tenderness, change in appetite, food craving, muscle pain, tinnitus, fatigue, oedema, bloating, social withdrawal, absenteeism from work/school, and poor work/academic performance ( 9 , 13 , 14 , 15 , 16 ). PMS management include administration of antidepressants like selective serotonin reabsorption inhibitors (SSRIs); others include non-steroidal anti-inflammatory drugs (NSAIDs) and OCPs, while non-drug management include intake of mineral supplements such as calcium and magnesium, intake of vitamins A, E and B 6 , exercising, yoga, and stress reduction programs ( 2 , 4 , 17 ).…”
Section: Introductionmentioning
confidence: 99%